Evolution of the Archaean Continental Crust in the North-eastern Fennoscandian Shield, Arctic Region: Isotope (U-Pb, SHRIMP, Sm-Nd and REE) Data Synthesis - Bayanova T.B.; Serov P.A.; Steshenko E.N.; Kunakkuzin E.L.; Borisenko E.S.; Drogobuzhskaya S.V.; Huber M. (Current Research on Geography, Earth Science and Environment Vol. 1, 2025)
The article provides a synthesis of new geological-geochemical and petrological data on Archaean rocks from the basement of the Central Kola and Murmansk Megablocks near Murmansk city. In addition, some rocks from the Kolmozero-Voronya Greenstone Belt have been studied. Particular attention is given to plagiogranites, tonalities, gneisses, amphibolites, late granitoids, intensely altered rocks and non-stratified rocks from the basement complex. The paper provides novel geological, petrochemical, U-Pb, SHRIMP, Sm-Nd and REE data on rocks and minerals. The new ages are correlated with ancient rocks of tonalite-trondhjemite-granodiorite complexes and grey gneisses in the Fennoscandian Shield and other world regions. The genesis of the oldest continental crust retains a marked trace in the Earth’s evolution over its 4.5 Ga history. The goals and objectives of the multidisciplinary research were to search for remnants of the ancient Archean continental crust on the Fennoscandian Shield. Precise U-Pb (ID-TIMS) and SHRIMP data on single zircon for paragneisses and TTG (3158.2±8.2 Ma) show the Central Kola and Belomorian (White Sea) megablocks of the Fennoscandian Shield to be 3.16 Ga and 3.70 Ga, respectively. The new ages of zircon from these megablocks indicate the origin of the discrete continental crust to be 3.16 and 3.70 Ga. It is close to the Nordsim zircon data on the Siurua TTG (Finland), i.e. 3.45 and 3.73 Ga in the core. The ancient Archean continental crust is known to exist on all continents of the world according to data (Arndt, 2023), and subduction processes have been recognised since 3.8 billion years ago (Arndt, 2023, Van Kranendonk et al., 2019).